Prediksi Jumlah Wisatawan Menggunakan Metode Random Forest, Single Exponential Smoothing dan Double Exponential Smoothing di Provinsi NTB - Ristu Haiban Hirzi; Umam Hidayaturrohman; Kertanah Kertanah; M. Hadiyan Amaly; Rody Satriawan (Jambura Journal of Probability and Statistics, 2023)
The aim of study is to forecast global tourist visits and compare the forecasting methods to determine the best method using random forest, single exponential smoothing and double exponential smoothing, respectively. These methods are applied in global tourist visit data in West Nusa Tenggara Province. Random forest, single exponential smoothing and double exponential smoothing are familiar methods and are frequently utilized in forecasting. In addition, the three methods have great accuracy for time series data, such as data of global tourist visits. The data used in this study is data of global tourist visits from 2014 to 2021 in West Nusa Tenggara province. Applying the random forest, single exponential smoothing and double exponential smoothing methods in forecasting, the result shows that double exponential smoothing method is the best, based on the smallest value of Mean Absolute Percentage Error (MAPE) of 325.759. The forecasting result found out that tourist visits will increase from previous time, starting from August, 2021 to July, 2021 with an estimated 847 to 1045 lives